INCREASING STUDENTS’ SPEAKING PERFORMANCE THROUGH THREE STEP INTERVIEW AT TEN GRADE OF SMK KARTIKATAMA 1 METRO ACADEMIC YEAR 2011- 2012 - Supriyadi - Supriyadi (Premise: Journal of English Education and Applied Linguistics, 2012)
English is taught earlier at the school. It is still learned continually until in the university. But unfortunately even though various methods and approaches have been tried out to reach the purpose, the result has not been satisfactory yet. Especially in speaking performance, students still has low scores. This study is aimed to describe the implementation of Three Step Interview and to increase students’ speaking performance. Objectives of the study are to describe the use of Three Step Interview towards student's speaking performance and to explore the increasing of students’ speaking performance through the Three Step Interview. The study was implemented in SMK Kartikatama 1 Metro, especially class X TKJ 2 using a classroom action research. The writer took 28 students as the subject. The data was a qualitative and the source of data taken from oral test. It used observation to collect the data. The techniques of analyzing data were reducing the data, presenting the data, and verifying the data.